Turkey into the European Union: Past Challenges and Future Prospects - Murat Metin Hakki (Romanian Journal of European Affairs, 2006)
This paper aims to analyze the impact that the EU accession process has already had on Turkey’s foreign policy since the acceptance of that country’s ‘candidacy’ for EU membership in 1999. It also endeavors to highlight the potential challenges ahead for eventual membership, while commenting on the problems that Turkey may face in its future negotiations with the EU, with particular emphasis on the areas in which Turkish Foreign Policy (TFP) may need ‘further’ adaptation.